2019
DOI: 10.1186/s13756-019-0665-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance of carbapenemase-producing Pseudomonas aeruginosa at three medical centres in Cologne, Germany

Abstract: BackgroundPseudomonas aeruginosa is a common pathogen causing hospital-acquired infections. Carbapenem resistance in P. aeruginosa is either mediated via a combination of efflux pumps, AmpC overexpression, and porin loss, or through an acquired carbapenemase. Carbapenemase-producing P. aeruginosa (CPPA) strains are known to cause outbreaks and harbour a reservoir of mobile antibiotic resistance genes, however, few molecular surveillance data is available. The aim of this study was to analyse the prevalence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
3
23
0
1
Order By: Relevance
“…In fact, a limitation of our study is the restriction of the reference method to detect only the most common carbapenemase-encoding genes, including class A (KPC, GES, NMC-A/IMI, BIC, SME), class B (VIM, NDM, IMP), and class D (Oxa-48, Oxa-23, Oxa-24) carbapenemases [17,31]. Although being the most prevalent and clinically relevant determinants of carbapenemase-mediated resistance in Germany [32][33][34][35], the presence of carbapenemases not covered by the PCR assay employed cannot be excluded. To compensate for the potential sensitivity limitation, all PCR-negative isolates were additionally tested using a phenotypic carbapenemase assay (i.e., CIM; [21]).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a limitation of our study is the restriction of the reference method to detect only the most common carbapenemase-encoding genes, including class A (KPC, GES, NMC-A/IMI, BIC, SME), class B (VIM, NDM, IMP), and class D (Oxa-48, Oxa-23, Oxa-24) carbapenemases [17,31]. Although being the most prevalent and clinically relevant determinants of carbapenemase-mediated resistance in Germany [32][33][34][35], the presence of carbapenemases not covered by the PCR assay employed cannot be excluded. To compensate for the potential sensitivity limitation, all PCR-negative isolates were additionally tested using a phenotypic carbapenemase assay (i.e., CIM; [21]).…”
Section: Discussionmentioning
confidence: 99%
“…In stark contrast, the 2015–2017 CR- P. A study by Schäfer et al. at three medical centers in Germany revealed that 30.6% (19/62) of the samples harbored either bla VIM-1 (n = 2) or bla VIM-2 (n = 17) genes ( Schäfer et al., 2019 ). The bla VIM carriage rate among CR- P. aeruginosa isolates was similar to that in the 2007–2009 survey conducted in Uganda (32%) ( Kateete et al., 2016 ), and that in the 2015–2016 survey of Dubai hospitals in the United Arab Emirates (32%) ( Moubareck et al., 2019 ).…”
Section: Resistance Mechanisms and Case-fatality Rates Due To Importa...mentioning
confidence: 99%
“…baumannii is a multidrug-resistant nosocomial pathogen that causes severe infections among patients especially in ICU and can hydrolyze various β-lactam antibiotics by different enzymes such as carbapenemases [131,132] . Among bacteria, resistance to carbapenems, especially imipenem, has been reported from various countries as well as in Iran [133][134][135] . Recently due to resistance of A. baumannii to a wide range of antimicrobial agents, raise a concern on controlling lifethreatening infections worldwide [136] .…”
Section: Discussionmentioning
confidence: 99%